Análise comparativa do Módulo de elasticidade calculado segundo diferentes Normas - Cabral, L.; Monteiro, E.; Helene, P. (Revista ALCONPAT, 2014)
This paper evaluates the suitability of the diagram of dosage of concrete in relation to thestatic and dynamic elasticity moduli. It also compares models of prediction of static modulusbased on the compressive strength. A comparative analysis was carried out amongexperimental values and those predicted by some standards, evaluating the accuracy of thelatter. The ACI 318:2014 was the standard that presented the closest results compared toNBR 6118:2014. On the other hand, the standards EUROCODE – 2:2004, DIN 1045. The fibMODEL CODE 2010 standard overestimated the values relative to the other standards. Thedynamic elasticity modulus, measured by ultrasonic waves, was also compared to the staticmodulus, and it proved as a fast and non-destructive alternative route to evaluate the staticelasticity modulus of concrete.Keywords: Modulus of elasticity, compressive strength, dosage diagram, prevision models.